Pendampingan Penggunaan E-Commerce Kerajinan Anyam Khas Melayu Pesisir di Pantai Cermin Serdang Bedagai - Irfandi Irfandi; Adek Cerah Kurnia Aziz; Taufik Hidayat; Mukti Hamjah Harahap; Deo Demonta Panggabean; Dedy Husrizal Syah (Jurnal Pengabdian Pada Masyarakat, 2021)
ASSISTANCE IN THE USE OF E-COMMERCE FOR COASTAL MALAY TYPICAL WEAVING CRAFTS AT PANTAI CERMIN SERDANG BEDAGAI. The aim of this service program is to serve the efforts of a group of craftsmen who are handicraftsmen of typical coastal Malay weaving and accessories in improving their group knowledge and skills. In addition, it increases the quality and quantity of products as well as product variations without eliminating the uniqueness of the mirror coastal cultural products. And what is no less important, marketing which is very limited to traditional concepts can not much increase their income and business development. The method used in realizing this is the team compiling programs in the form of knowledge transfer and ongoing mentoring. From the data in the table, it can be seen for IT-based Marketing Strategy Training and Worksop which has quite good competence (> 80) Dominates with only 16 and 11 participants while for the less category as many as 8 and 3 people. Furthermore, starting to build cooperation with the government and the private sector to prepare products to become regional icons of superiority as well as leaders in the fields of cooperatives and BUMDES. This activity is planned to be carried out using the approach of training methods, educational assistance, counseling, production training, business management training and equipment design. The team involved in this activity comes from 3 different faculties which have their respective functions and expertise.